Prevalence of anemia among non-pregnant andpregnant women of reproductive age in Nepal - Bhandary, Shital; Shrestha, A (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: The prevalence of anaemia among pregnant women in developing countries is high. Iron deficiency is one of the major causes of nutritional anemia worldwide. In order to address the problem of anemia in Nepal, government of Nepal introduced the Iron Supplementation and Intensification Programs. The 2006 Nepal Demographic and Health Survey evaluated these programs and revealed the reduction in the prevalence of anemia among women of reproductive age. However, reduction on prevalence of anemia among the non-pregnant and pregnant women has not been studied separately so far. Thus, this study aims to explore the 2006 Nepal Demographic and Health Survey (NDHS) data to study the change in the prevalence of anemia among non-pregnant and pregnant women of reproductive age.Methods: The data is taken from the 2006 Nepal Demographic and Health Survey (NDHS) which is a nationally representative survey of 10647 women of reproductive age or 15-49 years. Out of them 604 were pregnant at the time of the survey. Hemoglobin level is adjusted for the altitude and daily cigarettes smoking is used in this study. Using the adjusted hemoglobin level, anemia is classified into four categories i.e. severe, moderate, mild and any anemia.Results: The prevalence of anemia among the non-pregnant reproductive age women is found to be 35.8%. The highest prevalence is observed for Far-Western terai (67.1%) followed by Mid-Western terai (59.4%), Central terai (55.5%) and Western terai (47.15%). Mean hemoglobin (Hb) level is found to be less than 12 g/dl at these regions. The prevalence of severe anemia among non-pregnant women of reproductive age at national and eco-development regions is less than 2%, moderate anemia is 5.6% and mild anemia is 29.8%.The overall prevalence of anemia among the pregnant reproductive age women is found to be 42.7%. The highest prevalence is again observed for Far-Western terai (69.2%) followed by Central terai (55.2%) and Western terai (52.1%). The mean h level is less than 11 g/dl at Central, Western, Mid-Western and Far-Western terai regions. Prevalence of severe anemia among pregnant women of Western terai and Mid-western terai is found to be more than 2%. Furthermore, Mid-western hill and Central terai also has equal or more than 1.5% prevalence of severe anemia among pregnant women of reproductive age.Conclusion: There are some eco-development regions where anemia prevalence was found to be less in the pregnant women than the non-pregnant women and vice-versa. This warrants an immediate intervention policies and programs from the governmental and non-governmental agencies. Even though Nepal has reduced the prevalence of anemia among non-pregnant and pregnant women of reproductive age, it is required needs to further decrease the anemia prevalence in order to reduce the maternal mortality in the country and meet the target 5a of MDG Goal 5 on maternal health.